2005
DOI: 10.1116/1.1897704
|View full text |Cite
|
Sign up to set email alerts
|

Low- and high-resistivity silicon substrate characterization using the Al/silicon-rich oxide/Si structure with comparison to the metal oxide semiconductor technique

Abstract: High-resistivity silicon substrates (HRS, NB<1014cm−3) are commonly used, especially in optoelectronic integrated circuits. However, standard metal oxide semiconductor (MOS) characterization methods fail to predict correctly the dopant concentration and lifetime. This is due to the high resistance in series with the MOS capacitor, which causes an erroneous capacitance measurement at high frequency. To overcome this restriction, a different characterization method is proposed, using the electronic transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Härkönen et al (Härkönen et al, 2006) studied the lifetime of high resistivity silicon under low and high injection levels of carriers. They found that for high resistivity silicon the recombination lifetime is longer than 1 ms. Just for reference in our group, generation lifetime of high resistivity silicon was estimated to be between 1 and 2 ms (Luna et al, 2005). Then, a value of diffusion of 0.114 cm, or 1140 m is calculated.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Härkönen et al (Härkönen et al, 2006) studied the lifetime of high resistivity silicon under low and high injection levels of carriers. They found that for high resistivity silicon the recombination lifetime is longer than 1 ms. Just for reference in our group, generation lifetime of high resistivity silicon was estimated to be between 1 and 2 ms (Luna et al, 2005). Then, a value of diffusion of 0.114 cm, or 1140 m is calculated.…”
Section: Analysis and Discussionmentioning
confidence: 99%